1975
DOI: 10.1073/pnas.72.11.4631
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Escherichia coli treated with colicin K.

Abstract: (3) have shown the arrest of synthesis of macromolecules to be a consequence of the lowering of cellular ATP: in uncA mutants, which lack the Mg2+,Ca2+-activated ATPase (ATP phosphohydrolase, EC 3.6.1.3), the colicin failed to lower ATP levels and synthesis of macromolecules continued. Both transport of proline and of glutamine, apparently coupled to different forms of energy (4), were uncoupled by colicin K in the uncA mutants.Since synthesis of macromolecules continued in colicintreated uncA cells, it was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…A specific role for K+ and Mg2+ ions in protecting bacteria that have adsorbed colicin against subsequent death has been described recently (Kopecky, Copeland & Lusk, 1975). In contrast, the results presented here demonstrate that in general all ions have a similar protective effect on colicin-treated bacteria.…”
Section: Colicin K Adsorption =7 Discussioncontrasting
confidence: 55%
“…A specific role for K+ and Mg2+ ions in protecting bacteria that have adsorbed colicin against subsequent death has been described recently (Kopecky, Copeland & Lusk, 1975). In contrast, the results presented here demonstrate that in general all ions have a similar protective effect on colicin-treated bacteria.…”
Section: Colicin K Adsorption =7 Discussioncontrasting
confidence: 55%
“…For colicins El and K, which result in a rapid effliux of K+ and Mg2+ (4,10,16), viability could be restored by growth on K+-, Mg2+-supplemented medium thus artificially maintaining physiological levels intracellularly (13). K+ leakage from morganocin-treated cells was gradual, and growth on supplemented medium did not restore viability.…”
Section: K Was Determined By Its B Emission In a Packardmentioning
confidence: 89%
“…K+ leakage from morganocin-treated cells was gradual, and growth on supplemented medium did not restore viability. In this respect it appeared that the mode of action of morganocin 174 more closely resembled that of colicin Ib (13).…”
Section: K Was Determined By Its B Emission In a Packardmentioning
confidence: 95%
See 1 more Smart Citation
“…These authors observed an enhancement of toxin action when adenosine 5'-diphosphate was incorporated in the plate medium, and the enhancement was reversed by the addition of calcium ions. Furthermore, the killing effect of several bacteriocins is strongly affected by the ionic composition of the plate medium; in particular, monovalent cations (4,11) and magnesium ions (4) Preparation ofthe killer toxin and toxin assay. Cells of P. kluyveri 1002 were grown, and 100-fold concentrated solutions of the toxin were prepared as described previously (6a).…”
mentioning
confidence: 99%